On the spaces of Fibonacci difference absolutely p-summable, null and convergent sequences - Başarir, Metin; Başar, Feyzi; Kara, Emrah Evren (Sarajevo Journal of Mathematics, 2024)
Let 0<p<1. In the present paper, as the domain of the band matrix F defined by the Fibonacci sequence in the classical sequence spaces _p, c_0 and c, we introduce the sequence spaces _p(F), c_0(F) and c(F), respectively. Also, we give some inclusion relations and construct the bases of the spaces c_0(F) and c(F). Finally, we compute the alpha, beta, gamma duals of these spaces and characterize the classes (_p(F),μ) of infinite matrices with μ{_∞,c,c_0}.